Photonics North 2013 2013
DOI: 10.1117/12.2033655
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation of chiral-modified silver nanoparticles

Abstract: Various approaches for the optical detection of chiral compounds have been developed due to their natural optical activity. Since the advantages of second harmonic generation (SHG) on noble-metal nanoparticles (NPs) have been observed, it would be interesting to study the nonlinear phenomena from chiral compounds attached Ag NPs. In the present work, we fabricated chiral-modified Ag NPs based on the self-assembly process of cysteine and Ag, and carried out the investigation on SHG on modified and unmodified Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found that the interference fringes in the p-p and s-p polarizations had almost an opposite phase compared to p-s, attributed to the difference for the transformation between achiral and chiral components. Another study utilized the chiral response from L-cysteine and D-cysteine that were adsorbed onto the surface of silver nanoparticles (81). SHG was used to measure the optical nonlinearity of the system and the enantiomers were found to have opposite responses at 45 • and −45 • output polarizations.…”
Section: Detecting Biomolecular Interactions Using Chiralitymentioning
confidence: 99%
“…They found that the interference fringes in the p-p and s-p polarizations had almost an opposite phase compared to p-s, attributed to the difference for the transformation between achiral and chiral components. Another study utilized the chiral response from L-cysteine and D-cysteine that were adsorbed onto the surface of silver nanoparticles (81). SHG was used to measure the optical nonlinearity of the system and the enantiomers were found to have opposite responses at 45 • and −45 • output polarizations.…”
Section: Detecting Biomolecular Interactions Using Chiralitymentioning
confidence: 99%